2018
DOI: 10.1186/s12890-018-0769-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells from pulmonary endarterectomy specimens possess a high angiogenic potential and express high levels of hepatocyte growth factor

Abstract: BackgroundImpaired angiogenesis is assumed to be an important factor in the development of chronic thromboembolic pulmonary hypertension (CTEPH). However, the role of endothelial cells (ECs) in CTEPH remains unclear. The aim of this study was to investigate the angiogenic potential of ECs from pulmonary endarterectomy (PEA) specimens.MethodsWe isolated ECs from PEA specimens (CTEPH-ECs) and control EC lines from the intact pulmonary arteries of patients with peripheral lung cancers, using a MACS system. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In this study, we showed that CTEPH-EC also grew at a consistently faster rate and presented higher number of Ki-67 + cells when compared to healthy endothelial cells. This result is in line with previous publications in which they also showed greater proliferation capacity of CTEPH-EC denoting the involvement of endothelial cells in pulmonary artery occluding lesions 10,20 . In this study, we additionally demonstrated that CTEPH-EC had a significantly higher clonogenic potential and could survive for many more cell culture passages without losing their proliferative potential and phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we showed that CTEPH-EC also grew at a consistently faster rate and presented higher number of Ki-67 + cells when compared to healthy endothelial cells. This result is in line with previous publications in which they also showed greater proliferation capacity of CTEPH-EC denoting the involvement of endothelial cells in pulmonary artery occluding lesions 10,20 . In this study, we additionally demonstrated that CTEPH-EC had a significantly higher clonogenic potential and could survive for many more cell culture passages without losing their proliferative potential and phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we showed that CTEPH-EC also grew at a consistently faster rate and presented higher number of Ki-67 + cells when compared to healthy endothelial cells. This result is in line with a recent publication by Naito et al in which they showed greater proliferative potential of CTEPH-EC [17]. In this study, we additionally demonstrated that CTEPH-EC had a signi cantly higher clonogenic potential and could survive for many more cell culture passages without losing their proliferative potential and phenotype.…”
Section: It Has Been Recently Shown That Ecs Derived From Patients With Pah (Pah-ec) Have An Hyperproliferativesupporting
confidence: 93%
“…The existence of endothelial dysfunction in CTEPH pathogenesis is further supported by the fact that conditioned medium from CTEPH-derived PAECs, containing high levels of growth factors and inflammatory cytokines, increased PASMC proliferation and monocyte migration [ 157 ]. In addition, PAECs from CTEPH patients show an increased proliferation, altered angiogenic potential and metabolism, and apoptosis resistance [ 158 , 159 , 160 , 161 , 162 ]. Increased levels of soluble intracellular adhesion molecule-1 (ICAM1) in PAECs from CTEPH patients and in endarterectomy may contribute to EC proliferation and apoptosis resistance through its effect on cell survival pathways [ 161 ].…”
Section: Ec Dysfunction In Other Ph Groupsmentioning
confidence: 99%